Public Relations dalam Membina Hubungan dengan Media - Diajeng Herika; Poppy Ruliana (Inter Komunika, 2018)
The main purpose of this paper is to know and examine the importance of the role of public relations in developing media relations, both traditional media and social media used to build the image or reputation of the company. Media relations involves collaborating with the media in the form of printed media, electronic media and online media to inform the mission, policies and practices of the organization in a positive, consistent and reliable way. Typically, this means coordinating directly with the people responsible for producing news and features in the mass media. 'The purpose of media relations is to maximize positive coverage in the mass media